2014
DOI: 10.1167/iovs.14-14394
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Induced Chemokine Expression in Uveal Melanoma Cell Lines Stimulates Monocyte Chemotaxis

Abstract: Cytokines derived from activated T cells shifted the UM cell transcriptome toward a more inflammatory state, including upregulation of several chemokines, which led to an increased migration of monocytes. Therefore, UM cells might actively participate in generating a tumor-promoting inflammatory microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…There is sufficient evidence to show that initial release of chemokines such as CCL2, GM-CSF [58] mark a potentially irreversible turning point for tumor infiltration, immunological evasion, and tumor immune support [29,59,60]. Natural plant-derived chemicals that can downregulate CCL2 or act as CCR2 receptor antagonists [61] such as luteolin [62] esculetin [63] or EGCG [64,65] typically result in impaired migration, less proclivity for metastasis [66] enabling greater efficacy of immunotherapies and chemotherapy drugs [65].…”
Section: Discussionmentioning
confidence: 99%
“…There is sufficient evidence to show that initial release of chemokines such as CCL2, GM-CSF [58] mark a potentially irreversible turning point for tumor infiltration, immunological evasion, and tumor immune support [29,59,60]. Natural plant-derived chemicals that can downregulate CCL2 or act as CCR2 receptor antagonists [61] such as luteolin [62] esculetin [63] or EGCG [64,65] typically result in impaired migration, less proclivity for metastasis [66] enabling greater efficacy of immunotherapies and chemotherapy drugs [65].…”
Section: Discussionmentioning
confidence: 99%
“…Among these T-cell classifier genes are obligate T-cell markers such as CD3 and CD8. Also lymphocyte-attracting chemokines like CCL5 are expressed by T cells and found to be present in the T-cell classifier (25). T-cell-correlated genes is actually not expressed by T cells (Fig.…”
Section: Integration Of T-cell Count With the Expression Profile Of Umentioning
confidence: 95%
“…It should be considered that several of these cytokines may exert immune-suppressive and M2-polarizing effects. In addition, co-culture of UM cells with activated T cells upregulated the expression of chemokines and cytokines such as CXCL8, CXCL9, CXCL10, CXCL11, CCL2, CCL5, VEGF, and granulocyte–macrophage colony-stimulating factor (GM-CSF), which coincided with an enhanced ability to stimulate monocyte chemotaxis [269]. These data suggested that the cross-talk between tumor cells and T cells may result in the recruitment of pro-tumoral macrophages.…”
Section: Inflammationmentioning
confidence: 99%